2017
DOI: 10.1002/jnr.24133
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP2R1 rs10766197 with MS risk and disease progression

Abstract: The findings of our study open new perspectives for a role of CYP2R1 in both risk and progression of MS, with sex-related differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 36 publications
2
32
1
Order By: Relevance
“…Le Mokry et al (2015) identified SNPs associated with 25(OH)D level from SUNLIGHT, the largest ( n = 33,996) genome-wide association study to date for vitamin D. Four SNPs were genome-wide significant for 25(OH)D levels, and all four SNPs lay in, or near, genes strongly implicated in separate mechanisms influencing 25(OH)D. The authors found out that the count of the 25(OH)D-decreasing alleles across these four SNPs was strongly associated with a lower 25(OH)D level. Other recent perspectives [95] confirmed the research by Ahn et al [93]; it seems that there are strong links between the 25(OH)D levels and the genotyping of CYP2R1- and NAD-synthetase (NADSYN1-SNPs) in MS patients. The analysis revealed lower 25(OH)D concentrations in MS patients and an association of rs10766197 CYP2R1 SNP with MS risk.…”
Section: Vitamin D Deficiency and Multiple Sclerosis: Role In The supporting
confidence: 60%
See 3 more Smart Citations
“…Le Mokry et al (2015) identified SNPs associated with 25(OH)D level from SUNLIGHT, the largest ( n = 33,996) genome-wide association study to date for vitamin D. Four SNPs were genome-wide significant for 25(OH)D levels, and all four SNPs lay in, or near, genes strongly implicated in separate mechanisms influencing 25(OH)D. The authors found out that the count of the 25(OH)D-decreasing alleles across these four SNPs was strongly associated with a lower 25(OH)D level. Other recent perspectives [95] confirmed the research by Ahn et al [93]; it seems that there are strong links between the 25(OH)D levels and the genotyping of CYP2R1- and NAD-synthetase (NADSYN1-SNPs) in MS patients. The analysis revealed lower 25(OH)D concentrations in MS patients and an association of rs10766197 CYP2R1 SNP with MS risk.…”
Section: Vitamin D Deficiency and Multiple Sclerosis: Role In The supporting
confidence: 60%
“…Several genome-wide association studies (GWAS) and gene-candidate studies have investigated the influence of the specific genetic polymorphisms of vitamin D metabolites on the 25(OH)D levels, and their susceptibility to MS; one study found [92] an association between the short variant of the VDR protein (F allele) and a genetic predisposition to lower 25(OH)D levels, but not to a higher risk of MS; in a GWAS of 4501 European patients [93], single-nucleotide polymorphisms (SNPs) of the gene encoding components of the vitamin D binding protein were associated with 25(OH)D concentrations, or with the genes involved in vitamin D synthesis or activation; moreover, a genetically lowered 25(OH)D level was strongly associated with increased MS risk and progression in two studies [94,95]. …”
Section: Vitamin D Deficiency and Multiple Sclerosis: Role In The mentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of over 7000 individuals with MS, a genetic burden score was not associated with disability . Other smaller studies have reported associations of several genetic variants and progression of disability but have not yet been replicated …”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 94%